Metagrating-Based Terahertz Polarization Beam Splitter Designed by Simplified Modal Method - Ma, Xinyu; Li, Yanfeng; Lu, Yongchang; Han, Jiaguang; Zhang, Xixiang; Zhang, Weili (Frontiers in Physics, 2020)
Terahertz waves are finding important applications in diverse fields, and meanwhile the manipulation of terahertz waves calls for the development of various functional devices. Here, we have designed and fabricated a metagrating-based polarization beam splitter for terahertz waves using the simplified modal method. By only considering two propagation modes and treating the grating as a Mach-Zehnder interferometer, the method can greatly simplify the reverse grating design process. The parameters of the grating are first obtained under the guidance of the simplified modal method and then improved upon by the finite element method. The fabricated device is finally experimentally demonstrated with a terahertz time-domain spectroscopy system. The diffraction efficiencies of the polarization beam splitter at 0.9 THz are measured to be 69% and 63% for TE and TM waves relative to that of a silicon plate, respectively. The corresponding extinction ratios are 12 dB and 17 dB for TE and TM waves. The experiment results agree well with the simulations.